Manusia dalam Perspsektif Agama Islam - sada, Heru Juabdin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Humans are creatures of Allah the Almighty, created in a perfect state bentuk yang. Humans are spiritual beings who would have undergone various phases of events in his  life before  birth,  present,  or after death.  This sentence  may seem  too philosophical,  but actually  is a  term that  is simple  to understand.  Spiritual is  a psychological aspect which was then able to give strength to the people to be better able to understand life. Interest Man was created to implement the values of the divine that contain lots of serious benefits in life. Humans carry the mission mandate from Allah SWT. that must be implemented in real life activities.While the close relationship of man with Islam the man has the main task of which is to worship only God. All forms of worship that do man in various ways, all of it would go back just to us.  Submissive and obedient to  Allah, by becoming Caliph practice  their  religion,  and  a  few  other  things  ranging  from  the  largest  to  the smallest thing that included worship is not something that is lightweight, can be done by  playing  let  alone  to  deny  it.  Need  extra  effort,  and  spirit  strong  when  faith  is weakening, and the enormous responsibility later in the day of Judgement on what we have done in the world.